Lipid Nano-System Based Topical Drug Delivery for Management of Rheumatoid Arthritis: An Overview - Komal Diliprao Dhule; Tanaji Dilip Nandgude (Tabriz University of Medical Sciences, 2023)
The overall purpose of rheumatoid arthritis (RA) treatment is to give symptomatic alleviation; there is no recognized cure for RA. Frequent use of potent drugs like non-steroidal anti-inflammatory drugs (NSAIDs) and disease-modifying antirheumatic drugs (DMARDs), lead to various adverse effects and patient compliance suffers. On the other hand, there are many drawbacks associated with traditional methods, such as high first pass, high clearance rate, and low bioavailability. Drug administration through the skin can be a promising alternative to cope with these drawbacks, increasing patient compliance and providing site-specific action. The stratum corneum, the uppermost non-viable epidermal layer, is one of the primary limiting barriers to skin penetration. Various nanocarrier technologies come into play as drug vehicles to help overcome these barriers. The nanocarrier systems are biocompatible, stable, and have a lower cytotoxic impact. The review discusses several lipid-based nanocarrier systems for anti-rheumatic medicines for topical administration it also discusses in-vivo animal models for RA and provides information on patents granted.